1990
DOI: 10.1530/jrf.0.0900037
|View full text |Cite
|
Sign up to set email alerts
|

Fate and turnover rate of ovarian follicular cysts in dairy cattle

Abstract: Non-lactating, multiparous dairy cows diagnosed as having cysts by palpation per rectum were used. Cysts were induced with oestradiol-17 beta (15 mg) and progesterone (37.5 mg) dissolved in ethanol and injected s.c. twice daily for 7 days. Following initial diagnosis of cysts, ovaries were exposed by midventral laparotomy, and the perimeter of the base of each cyst was marked with subepithelial injections of charcoal. Ovaries were removed from cows by transvaginal incision at 10 days (Group 1; N = 8), 20 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 11 publications
4
47
0
1
Order By: Relevance
“…Numerous previous studies have hormonally induced cows to have follicular cysts, using large doses of exogenous E 2 . About 50% of cows became anovular following these treatments (Cook et al 1990, Hamilton et al 1995, Calder et al 1999. Cows with induced follicular cysts appear to be in a physiological state in which high circulating E 2 either produces a delayed However, this is the first study, to our knowledge, that has shown that this lack of hypothalamic responsiveness to E 2 and follicular cysts can be induced by the normal increase in E 2 simply by preventing the post-ovulatory rise in circulating P 4 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Numerous previous studies have hormonally induced cows to have follicular cysts, using large doses of exogenous E 2 . About 50% of cows became anovular following these treatments (Cook et al 1990, Hamilton et al 1995, Calder et al 1999. Cows with induced follicular cysts appear to be in a physiological state in which high circulating E 2 either produces a delayed However, this is the first study, to our knowledge, that has shown that this lack of hypothalamic responsiveness to E 2 and follicular cysts can be induced by the normal increase in E 2 simply by preventing the post-ovulatory rise in circulating P 4 .…”
Section: Discussionmentioning
confidence: 86%
“…Development of an appropriate model is essential for studies on the underlying physiology of follicular cysts. Several different methods have been used to induce animals into an anovular condition resembling follicular cysts including estradiol (E 2 ) treatment during diestrus (Wiltbank et al 1961, Nadaraja & Hansel 1976, multiple treatments with high doses of progesterone (P 4 ) and E 2 (Erb et al 1973, Cook et al 1990, Hamilton et al 1995, Calder et al 1999 and prolonged E 2 exposure (Dobson et al 1996(Dobson et al , Ö zturk et al 1998. Follicular cysts can also be induced with a single E 2 injection if E 2 is given at a time when the gonadotropin-releasing hormone (GnRH)/luteinizing hormone (LH) surge will occur in the absence of a potentially ovulatory follicle .…”
Section: Introductionmentioning
confidence: 99%
“…Interval between 1st treatment and 1st insemination. 3. Interval between 1st insemination after the 1st treatment and conception.…”
Section: Rectal Examination For Pregnancy Detection Took Placementioning
confidence: 99%
“…Roberts (20) defined COD as the persistence of an anovulatory follicular structure (> 2.5 cm) in the absence of luteal tissue, and Cook et al (3) defined COD as the presence of non-ovulatory follicles larger than 2.0 cm for at least 10 days without development of a corpus luteum. However, Farin (10) noted that cysts sometimes occur simultaneously with a corpus luteum.…”
Section: Introductionmentioning
confidence: 99%
“…This ovarian disorder is one of the most important causes of infertility in cattle, and is attended with considerable economic loss because of its high incidence [11]. Cook et al [4] reported that steroid-induced follicular cysts in cattle were not static structures, but regressed to be replaced with other cystic structures. Furthermore, previous investigations [7,17] showed that spontaneously occurring ovarian cysts also exhibit a turnover of cysts, and suggested that the absence of a preovulatory surge of luteinizing hormone (LH) causes ovarian cysts [3,7,17].…”
mentioning
confidence: 99%